Sustainability of Indonesian P2P Lending: Determinants of Continued Use with Expectation Confirmation Model Integration - Santi, Fitri; El Wida, Dharma Bima; Rahmayanti, Dewi (Jurnal Aplikasi Manajemen, 2025)
Peer-to-peer lending has emerged as a leading innovation in Indonesia's financial technology landscape, transforming traditional lending practices with its efficiency and accessibility. This study aims to uncover the key factors influencing users' intention to sustain use of P2P lending platforms amid rising adoption rates. Using the Expectation Confirmation Model (ECM), this study explores the impact of financial self-efficacy (FSE), perceived risk (PR), and digital financial literacy (DFL) on user satisfaction(ST) and sustained engagement or continued intention (CI). In addition, this study discusses the positive and negative impacts that may arise from this evolving lending model, contributing to the discussion on financial inclusion and the sustainability of fintech innovation in Indonesia. This study used Partial Least Squares (PLS) regression to test the proposed hypotheses. The results show that financial self-efficacy, perceived risk, and digital financial literacy positively affect user satisfaction and the intention to continue using P2P lending. Satisfaction and perceived benefits are the main drivers of user retention. Financial literacy education, transparency in risk management, and the development of user-friendly features can increase trust and loyalty to the platform.